Peningkatan Keunggulan Produk Melalui Penyuluhan Strategi Pemasaran Produk Umkm Desa Kadubereum Kecamatan Pabuaran, Kabupaten Serang - nugrahini kusumawati; Surti Zahra (Universitas Serang Raya, 2021)
Abstract Increasing the resilience of one's family with an increase in economic resources for families. Kadubereum village has a lot of natural potential that can be processed by people to become processed products. UMKM problem in Kadubereum village has not been the amount of natural potential to be a product that has a selling value, and for those who already utilize the natural potential in the village is still constrained by the marketing of its products. To assist UMKM in providing solutions then the implementation methods used after the survey, then provide counseling on marketing strategies and product development training. The result is to add insight and public knowledge about marketing strategies and product development. Keywords: Enhanced product excellence, counseling, marketing strategies